Microencapsulated adult porcine islets transplanted intraperitoneally in streptozotocin‐diabetic non‐human primates. (17th August 2018) - Safley, Susan A.; Kenyon, Norma S.; Berman, Dora M.; Barber, Graham F.; Willman, Melissa; Duncanson, Stephanie; Iwakoshi, Neal; Holdcraft, Robert; Gazda, Lawrence; Thompson, Peter; Badell, I. Raul; Sambanis, Athanassios; et al.
Abstract: Background: Xenogeneic donors would provide an unlimited source of islets for the treatment of type 1 diabetes (T1D). The goal of this study was to assess the function of microencapsulated adult porcine islets (APIs) transplanted ip in streptozotocin (STZ)‐diabetic non‐human primates (NHPs) given targeted immunosuppression. Methods: APIs were encapsulated in: (a) single barium‐gelled alginate capsules or (b) double alginate capsules with an inner, islet‐containing compartment and a durable, biocompatible outer alginate layer. Immunosuppressed, streptozotocin‐diabetic NHPs were transplanted ip with encapsulated APIs, and graft function was monitored by measuring blood glucose, %HbA1c, and porcine C‐peptide. At graft failure, explanted capsules were assessed for biocompatibility and durability plus islet viability and functionality. Host immune responses were evaluated by phenotyping peritoneal cell populations, quantitation of peritoneal cytokines and chemokines, and measurement of anti‐porcine IgG and IgM plus anti‐Gal IgG. Results: NHP recipients had reduced hyperglycemia, decreased exogenous insulin requirements, and lower percent hemoglobin A1c (%HbA1c) levels. Porcine C‐peptide was detected in plasma of all recipients, but these levels diminished with time. However, relatively high levels of porcine C‐peptide were detected locally in the peritoneal graft site of some recipients at sacrifice. IV glucose tolerance tests demonstrated metabolic function, but the grafts eventually failed in all diabetic NHPs regardless of the type of encapsulation or the host immunosuppression regimen. Explanted microcapsules were intact, "clean, " and free‐floating without evidence of fibrosis at graft failure, and some reversed diabetes when re‐implanted ip in diabetic immunoincompetent mice. Histology of explanted capsules showed scant evidence of a host cellular response, and viable islets could be found. Flow cytometric analyses of peritoneal cells and peripheral blood showed similarly minimal evidence of a host immune response. Preformed anti‐porcine IgG and IgM antibodies were present in recipient plasma, but these levels did not rise post‐transplant. Peritoneal graft site cytokine or chemokine levels were equivalent to normal controls, with the exception of minimal elevation observed for IL‐6 or IL‐1β, GRO‐α, I‐309, IP‐10, and MCP‐1. However, we found central necrosis in many of the encapsulated islets after graft failure, and explanted islets expressed endogenous markers of hypoxia (HIF‐1α, osteopontin, and GLUT‐1), suggesting a role for non‐immunologic factors, likely hypoxia, in graft failure. Conclusions: With donor xenoislet microencapsulation and host immunosuppression, APIs corrected hyperglycemia after ip transplantation in STZ‐diabetic NHPs in the short term. The islet xenografts lost efficacy gradually, but at graft failure, some viable islets remained, substantial porcine C‐peptide was detected in the peritoneal graft site, and there was very little evidence of a host immune response. We postulate that chronic effects of non‐immunologic factors, such as in vivo hypoxic and hyperglycemic conditions, damaged the encapsulated islet xenografts. To achieve long‐term function, new approaches must be developed to prevent this damage, for example, by increasing the oxygen supply to microencapsulated islets in the ip space.